Perceptions, views and practices regarding antibiotic prescribing and stewardship among hospital physicians in Jakarta, Indonesia: a questionnaire-based survey - Limato, R; Nelwan, EJ; Mudia, M; Alamanda, M; Manurung, ER; Mauleti, IY; Mayasari, M; Firmansyah, I; Djaafar, R; Vu, HTL; van Doorn, HR; Broom, A; et al. (BMJ Publishing Group, 2022)
Objectives Antibiotic overuse is one of the main drivers of antimicrobial resistance (AMR), especially in low-income and middle-income countries. This study aimed to understand the perceptions and views towards AMR, antibiotic prescribing practice and antimicrobial stewardship (AMS) among hospital physicians in Jakarta, Indonesia. Design Cross-sectional, self-administered questionnaire-based survey, with descriptive statistics, exploratory factor analysis (EFA) to identify distinct underlying constructs in the dataset, and multivariable linear regression of factor scores to analyse physician subgroups. Setting Six public and private acute-care hospitals in Jakarta in 2019. Participants 1007 of 1896 (53.1% response rate) antibiotic prescribing physicians. Results Physicians acknowledged the significance of AMR and contributing factors, rational antibiotic prescribing, and purpose and usefulness of AMS. However, this conflicted with reported suboptimal local hospital practices, such as room cleaning, hand hygiene and staff education, and views regarding antibiotic decision making. These included insufficiently applying AMS principles and utilising microbiology, lack of confidence in prescribing decisions and defensive prescribing due to pervasive diagnostic uncertainty, fear of patient deterioration or because patients insisted. EFA identified six latent factors (overall Crohnbach’s α=0.85): awareness of AMS activities; awareness of AMS purpose; views regarding rational antibiotic prescribing; confidence in antibiotic prescribing decisions; perception of AMR as a significant problem; and immediate actions to contain AMR. Factor scores differed across hospitals, departments, work experience and medical hierarchy. Conclusions AMS implementation in Indonesian hospitals is challenged by institutional, contextual and diagnostic vulnerabilities, resulting in externalising AMR instead of recognising it as a local problem. Appropriate recognition of the contextual determinants of antibiotic prescribing decision making will be critical to change physicians’ attitudes and develop context-specific AMS interventions.